ANALISIS KEMAMPUAN SMASH FOREHAND TENIS MEJA PADA SISWA SMA NEGERI 4 KENDARI - Sariul Sariul; marsuna marsuna; Jud Jud (JURNAL EDUSCIENCE (JES), 2022)
The purpose of this study was to determine the analysis of the forehand smash ability of table tennis in SMA Negeri 4 Kendari students. The population is 19 people. While the sampling technique was carried out by total sampling technique, namely the entire population was sampled, so that in this study the sample consisted of 19 people. The instrument used to measure the forehand smash ability was a smash test 10 times. The data analysis technique used descriptive statistics of percentages. The results showed that the analysis of the table tennis forehang smash ability of SMA Negeri 4 Kendari students was obtained as many as 2 students with a percentage of 11% in the very good category, as many as 7 students with a percentage of 37% in the good category, as many as 5 students with a percentage of 26% are in the less category, and as many as 0 students with a percentage of 0% are in the less category. So it can be concluded that the analysis of the table tennis forehand smash ability of SMA Negeri 4 Kendari students is in the good category.